Zika virus infection of pregnant rats and associated neurological consequences in the offspring - Sherer, Morgan L. (PLoS One, 2019)
Zika virus (ZIKV) is a mosquito-borne flavivirus associated with microcephaly and other neurological disorders in infants born to infected mothers. Despite being declared an international emergency by the World Health Organization, very little is known about the mechanisms of ZIKV pathogenesis or the long-term consequences of maternal ZIKV infection in the affected offspring, largely due to the lack of appropriate rodent models. To address this issue, our lab has developed a working model of prenatal ZIKV infection in rats. In this study, we infected immune competent pregnant female rats with 10(5)–10(7) PFU of ZIKV (PRVABC59, Puerto Rico/Human/Dec 2015) in order to examine its pathogenesis in the dams and pups. We examined the febrile response and sickness behavior in the dams, in addition to neonatal mortality, microglia morphology, cortical organization, apoptosis, and brain region-specific volumes in the offspring. Here, we demonstrate that pregnant and non-pregnant female rats have a distinct febrile response to ZIKV infection. Moreover, prenatal ZIKV infection increased cell death and reduced tissue volume in the hippocampus and cortex in the neonatal offspring. For the first time, we demonstrate the efficacy and validity of an immunocompetent rat model for maternal ZIKV infection that results in significant brain malformations in the neonatal offspring.